Diplomasi Digital Dalam Mengembangkan UMKM Go Global Go Digital di Kepulauan Riau - Putri, Rizqi Apriani; Swastiwi, Anastasia Wiwik; Aleksa, Nabila Zazkia Zikra (Global Political Studies Journal, 2024)
The phenomenon of globalization is currently undergoing various digital transformations toward increasing access to information, community welfare, innovation, and productivity. The development of technology in this digitalization era provides quite important changes in people's lives, even digital diplomacy is used for negotiations. Digital diplomacy can provide public information and build relations between countries in International Relations. This research aims to gain an understanding of digital diplomacy, increasing MSMEs Go Global Go Digital amid the current development of technological flows and economic innovation in society. The research method used is qualitative descriptive a data collected will be analyzed from primary and secondary data sources such as books, articles, publications, reports, and other publication relevant to this study. At the end of 2019, the world was hit by the Covid-19 Pandemic which caused restrictions on mobility between countries. Due to the Covid-19 pandemic, there has been an increase in the use of digital technology. The government utilizes this digital technology to increase MSMEs with the slogan Go Global Go Digital which has been launched by Bank Indonesia since 2020. The application of digital technology can increase MSMEs in the global market. Riau Islands which has a strategic area bordering neighboring countries can be utilized in the development of MSMEs to penetrate the global market by expanding Cross Border Payment Connectivity cooperation. This research has an impact on digital diplomacy comprehensively. Keywords — Digital Diplomacy, Globalization, MSMEs